The Inhibitory Effect of Validamycin A on Aspergillus flavus - Napasawan Plabutong; Supanuch Ekronarongchai; Nattarika Niwetbowornchai; Steven W. Edwards; Sita Virakul; Direkrit Chiewchengchol; Arsa Thammahong (International Journal of Microbiology)
Aspergillus flavus is one of the most common isolates from patients with fungal infections. Aspergillus infection is usually treated with antifungal agents, but side effects of these agents are common. Trehalase is an essential enzyme involved in fungal metabolism, and the trehalase inhibitor, validamycin A, has been used to prevent fungal infections in agricultural products. In this study, we observed that validamycin A significantly increased trehalose levels in A. flavus conidia and delayed germination, including decreased fungal adherence. In addition, validamycin A and amphotericin B showed a combinatorial effect on A. flavus ATCC204304 and clinical isolates with high minimum inhibitory concentrations (MICs) of amphotericin B using checkerboard assays. We observed that validamycin A and amphotericin B had a synergistic effect on A. flavus strains resistant to amphotericin B. The MICs in the combination of validamycin A and amphotericin B were at 0.125 μg/mL and 2 μg/mL, respectively. The FICI of validamycin A and amphotericin B of these clinical isolates was about 0.25–0.28 with synergistic effects. No drug cytotoxicity was observed in human bronchial epithelial cells treated with validamycin A using LDH-cytotoxicity assays. In conclusion, this study demonstrated that validamycin A inhibited the growth of A. flavus and delayed conidial germination. Furthermore, the combined effect of validamycin A with amphotericin B increased A. flavus killing, without significant cytotoxicity to human bronchial epithelial cells. We propose that validamycin A could potentially be used in vivo as an alternative treatment for A. flavus infections.